Answer:
y = (x+3)^2 -1
Step-by-step explanation:
The vertex form of the equation is
y = a(x-h)^2 +k where (h,k) is the vertex
The vertex is (-3,-1)
y = a(x- -3)^2 -1
y = a(x+3)^2 -1
Pick another point (-2,0) and substitute it into the equation
0 = a(-2+3)^2 -1 to find a
0 =a(1)^2 -1
0 = a-1
1 = a
y = (x+3)^2 -1
Soldiers for the nation of Gilead. “Blessed Be the Fruit”: The standard greeting amongst Gilead residents. The traditional reply is “May the Lord open.” “Under His Eye”: The Gileadean equivalent of “Aloha” — it works as both a hello and a goodbye.
Answer:
Kaden had $17 at first
Step-by-step explanation:
Ben = x
Kaden = x - 10
x + 4
x - 10 + 4 = x -6
x - 6 =
x
9(x - 6) = 7x
9x - 54 = 7x
2x = 54
x = 27
x - 10 = 27 - 10 = 17
Answer:
here
Step-by-step explanation:
1 = B
4-(-3) that 3 is turned into a positive number
2 is b same reason
1/2 chance of one baby being a boy
1/2*7
7:2 chance